Consumption of Tamil Cinema in Malaysia : an analysis of Malaysian Tamil youth audiences / Thomas Jayaprakash Yesudhasan, N.V.Prasad and Shanthi Balraj - Yesudhasan, Thomas Jayaprakash; Prasad, N.V.; Balraj, Shanthi (UPENA, 2007)
Globalization has provided a new momentum to diasporic studies. Cultural products from the place of origin have been studied in diverse diasporic settings for their socio-cultural implications. In the Malaysian context, very little research work has been done on how Indian diaspora, particularly the young Malaysian Indians, read and consume Tamil films that are produced and distributed from Tamil Nadu, India. A study has been conducted at Universiti Sains Malaysia to explore the patterns of negotiations in the diasporic space by Indian youth in Malaysia. The participants for this study were drawn from Universiti Sains Malaysia in Penang, majority of them are from the Tamil speaking Indian diaspora. The study using qualitative audience analysis approach looks at how and why they choose certain films; their perceptions on the content, theme, story line; reflections of customs, culture and tradition. It revealed the nature and characteristics of the patterns of audience engagement with the Tamil cinema.